SISTEM INFORMASI PANDUAN WISATA SEJARAH DI KAWASAN BENTENG KUTO BESAK DAN MUSEUM SULTAN MAHMUD BADARUDDIN II, DENGAN INTEGRASI PROMOSI UMKM DAN KULINER - Muhammad Rafi Alfarizi; Giri Syawega; Muhammad Riyadhi Rangkuti (CV. Denasya Smart Publisher, 2026)
Historical tourism in Palembang City, particularly in the Benteng Kuto Besak (BKB) area and the Sultan Mahmud Badaruddin II Museum (SMB II), has significant educational potential. However, information related to historical narratives, museum collections, practical details such as ticket prices, as well as the locations of nearby micro, small, and medium enterprises (MSMEs) and culinary destinations remains fragmented. This condition results in a suboptimal tourist experience and limits the promotion of the local economy. Therefore, this study aims to develop a web-based historical tourism guide information system using the PHP framework Laravel, integrated with MSME and culinary promotion, and to evaluate its functionality and feasibility through Black Box Testing and User Acceptance Testing (UAT). The development method employed is Research and Development (R&D) using an Iterative Prototype model, enabling rapid refinement of geospatial functionalities and UI/UX design. The results indicate that the system was successfully implemented using an optimal Model–View–Controller (MVC) architecture, separating stable historical content modules from dynamic MSME and culinary directories. Geospatial functionality was implemented through integration with the Google Maps API, providing automatic geocoding for MSMEs and culinary locations as well as Haversine distance calculations, effectively transforming static address data into actionable navigation guidance. With this integration, the system functions not only as a structured historical education tool but also as a driver of the local economy, achieving a target System Usability Scale (SUS) score above 80 in UAT, indicating a very high level of usability.